2004
DOI: 10.1111/j.1360-0443.2004.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three models of alcohol craving in young adults: a cross‐validation

Abstract: Approach and avoidance inclinations toward alcohol are separable constructs, and their activation may not be invariably reciprocal. Craving can be defined as the relative activation of substance-related response inclinations along these two primary dimensions. There may be a threshold of intensity that separates mild from intense approach inclinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
140
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 60 publications
5
140
0
Order By: Relevance
“…The Approach and Avoidance of Alcohol Questionnaire (AAAQ, McEvoy et al, 2004) is a 14-item self-report questionnaire developed to assess the compulsive urge to drink alcohol and the avoidance towards alcohol. Participants had to indicate the extent to which they agreed or not with each item on a 9-point Likert scale ranging from "not at all" (0) to "very strongly" (8).…”
Section: Approach and Avoidancementioning
confidence: 99%
“…The Approach and Avoidance of Alcohol Questionnaire (AAAQ, McEvoy et al, 2004) is a 14-item self-report questionnaire developed to assess the compulsive urge to drink alcohol and the avoidance towards alcohol. Participants had to indicate the extent to which they agreed or not with each item on a 9-point Likert scale ranging from "not at all" (0) to "very strongly" (8).…”
Section: Approach and Avoidancementioning
confidence: 99%
“…Subsequent studies employed the AAAQ with different populations of drinkers and performed factor analysis on participants' responses. Each of these studies confirmed that approach and avoidance represent distinct underlying factors, although some studies with alcohol dependent patients Schlauch et al, 2013c; but see Klein and Anker, 2013) identified a single underlying factor to approach inclinations rather than the qualitative distinction between mild and strong approach that was reported in the initial study (McEvoy et al, 2004). Many of these studies demonstrated that both approach and avoidance inclinations are independently associated with drinking-related variables.…”
Section: Introductionmentioning
confidence: 81%
“…According to the ambivalence model of craving (Breiner et al, 1999;McEvoy et al, 2004), the decision to consume alcohol is determined by the balance between motivational inclinations to indulge ("approach") and to abstain ("avoidance"). Approach and avoidance inclinations might arise from the desire for intoxication or the wish to keep a clear head for the next day, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations